The Subject Matter of Mandate Contract as Defined by the Polish Civil Code – Polish Codification and Foreign Influence - Krzysztof KUBASIK (Communications of International Proceedings, 2020)
Contracts of mandate have a long history and date back to the law of ancient Rome. Over the centuries, mandate contract has been substantially modified, in particular with regard to its subject matter and admissibility of remuneration. Another important aspect is the historical connection between mandate contract and the power of attorney. Mandate contract has also undergone major changes in the Polish law. Under the current Civil Code, its subject matter is the performance of acts in law, which is a significant limitation compared to the previous model. The aim of the paper is to analyze its legal status and modifications made, including comparison of with the Swiss model which served as a benchmark for the Polish codification, in particular the mandate contract governing provisions set out in the 1933 Code of Obligations. However, adoption of solutions similar to the Swiss model caused a lot of interpretative confusion. In consequence, its legal status had to be amended and its subject matter narrowed down to the performance of legal acts. Ultimately, after long years, the Polish model took a different shape. The main goal of changes implemented in the Polish legal system was to prevent interpretative doubts created by the too wide contract’s subject matter. However, the objective has not been achieved.  In view of the above, the opinion that mandate contracts with broad subject matter, encompassing legal and factual acts, would be a better response to current social and economic needs is justified.
Keywords: mandate contract; service contract; Polish legal system; Swiss legal system; proper application of law